ABSTRACT MANUAL OF ANTI-ART DEFIES CRITICS - Will, Ralf G (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2024)
This article on ir-relevance of Art criticism and its perpetrators, the maligned re-viewers, explores how close Kurt Schwitter`s points of reference here are aligned to ANTOA, the New Theory of Art. Schwitters (pronounce Sh-wit-ash) as main exponent of Hannover`s circle of avantgarde artists in interregnum between World War I and II (ca 1920 to 1939), was an accomplished yet often misunderstood creator, busy in fields of painting, sculpting, graphic design and literature. Furthermore the link between Schwitter`s influential quote on the value of „Abstract Non-Art“ and 1950ies/60ies phenomena of theatrical performance are investigated. This as much as application of points 3 – old make new, 4 – abstraction, where does it come from and where does it lead to?and 5 – message and symbolism, in relation to ANTOA, come under the spotlight.I begin with an imaginary question from my series ROLE OF ARTIST IN SOCIETY, 24 INTERVIEWS FROM SOUTH AFRICA